Involvement of Membrane GRP78 in Trophoblastic Cell Fusion - Fradet, Sarah; Pierredon, Sandra; Ribaux, Pascale; Epiney, Manuella; Shin Ya, Kazuo; Irion, Olivier; Cohen, Marie (PloS one, 2012)
Glucose-regulated protein 78 (GRP78) is highly expressed in first trimester cytrophoblastic cells (CTBs), especially in syncytiotrophoblast (STB). However, the role of GRP78 in these cells has never been investigated. In this study, we have examined the role of GRP78 in trophoblast fusion using the Bewo choriocarcinoma cell line as a model of cytotrophoblast fusion. Down regulation of GRP78 by siRNA or chemical inhibitors and use of antibodies against GRP78 in culture medium significantly decreased forskolin-induced fusion capacity of Bewo cells suggesting the involvement of membrane GRP78 in trophoblast fusion. GRP78 expression was also studied in preeclamptic (PE) CTBs which are known to have lower fusion capacity compared to control CTBs. Interestingly, despite the increase of GRP78 mRNA in PE CTBs, membrane GRP78 is significantly decreased in PE CTBs compared to control CTBs, suggesting that relocation of GRP78 from the endoplasmic reticulum to cell surface is probably altered in PE CTBs. Our results imply that membrane GRP78 could play an important role in syncytialisation. They also suggest that deregulation of GRP78 expression or relocation at cell surface might be involved in pregnancy complication associated with defective syncytialisation, such as preeclampsia.